ADVANTAGES AND LIMITATIONS OF DISTANCE LEARNING - Gacov, Sanja (International Scientific Journal Vision, 2025)
How Digital Learning is going to Change Schools and Education Digital studying is a new technological advancement in the field of schooling that has since presented each positive and negative outcomes. While there have been various benefits including a various way of delivering content and multiplied research capacity, it has been particularly perturbing that there are related addiction and a shift from the traditional to on line learning settings. The outcome has resulted in a discount in the quality of education and college students tend to abscond classes opting to interact with their digital learning gadgets. It is thus crucial to formulate alternative and solution to the developing challenge that is threatening the quality of education in the long-term as the shift from the traditional learning setting become imminent. The recommended policy of change that is relevant in this case involves all stakeholders including parents and teachers engaging in the monitoring of use to avoid overindulgence while ensuring that the learners use the digital learning media for productive reasons. The area of interest will be on the adverse effects that digital education brings to schools and learning in the traditional setting with reports identifying that the whole system is a waste of resources.